Rogue drivers, typical cyclists, and tragic pedestrians: a Critical Discourse Analysis of media reporting of fatal road traffic collisions. Issue 6 (2nd November 2022) - Fevyer, David; Aldred, Rachel
ABSTRACT: In Britain, a third of road traffic fatalities are pedestrians or cyclists. Media reporting may play a key role in shaping how people interpret these events. We conduct in-depth Critical Discourse Analysis of a sample of 17 London Evening Standard articles, covering car-bicycle, car-pedestrian, and bicycle-pedestrian fatality collisions. Using Van Leeuwen's Social Actor model we find that drivers involved in collisions are backgrounded, except those who failed to stop, who are portrayed as exceptional. Pedestrian casualties are framed episodically, i.e. as individual incidents not linked to wider contexts. Cyclist fatalities are presented thematically, although this common theme was cycling itself, not infrastructure, policy, or driver behaviour. When involved in pedestrian fatality collisions, cyclists are directly described as participants, rather than referred to indirectly through their vehicle as drivers are. Thus, narratives tend to erase driver agency in collisions while highlighting agency for cyclists, and pedestrian deaths appear as isolated incidents rather than part of a wider structural pattern. We identify three key tropes: rogue drivers, typical cyclists, and tragic pedestrians. The analysis shows how these, and the reporting patterns identified here, help to reproduce assumptions about risk posed to others by different modes, and consequent responsibility for crashes.